Foresail - CubeSat platform and missions to higher orbits - Praks Jaan; Niemelä Petri; Anger Marius; Fetzer Anton; Clayhills Bruce; Cheremetiev Kiril; Lundén Ville; Jovanovic Nemanja; Vainio Rami; Janhunen Pekka; Kilpua Emilia; Palmroth Minna (United States, 2025)
Small affordable satellites have opened the opportunity for innovative small class science missions to Low Earth Orbit and beyond. Finnish Centre of Excellence in Research of Sustainable Space (FORESAIL) started a CubeSat program which aims to improve CubeSat technology radiation tolerance to explore the higher orbits and radiation belt. Currently, the Foresail satellite program consists of two development generations of CubeSat platforms, prepared for to different science missions. Two satellites, the Foresail-1 (FS1) and Foresail-1’ (FS1’) utilize the 3U CubeSat form factor and have been developed for Low Earth Orbit (LEO), whereas the Foresail-2 satellite aim towards a highly elliptical Geostationary Transfer Orbit (GTO) to study magnetic Ultra Low Frequency waves in the radiation belt region.
2023 XXXVth General Assembly and Scientific Symposium of the International Union of Radio Science (URSI GASS)